Reescritas poéticas, em “A meditação sobre o Tietê” - Souza, Cristiane Rodrigues de (eLyra, 2018)
Mário de Andrade, in "A meditação sobre o Tietê", a long poem published in Lira paulistana (1945), rewrites, in verses, expressions of the Brasilian popular tradition, recovering traces of the dramatic dances, popular dances studied by the poet-researcher. At the same time, by reading the poems of Percy Bysshe Shelley and Walt Whitman, present in his library, the Brazilian modernist approaches, in his poem, themes dear to the British poet and to the American bard. In this way, he encounters fragmentation, love, death and resurrection, elements that mark his poetry, both in the ballets of the people and in the verses read, showing the multifaceted character of the Brazilian, as well as the fragmented face of the lyrical self.